Rehabilitasi Sebagai Pemenuhan Restorative Justice Terhadap Penyalahgunaan Narkotika di BNN Kabupaten Tana Toraja - Panggalo, Iindarda S.; M. Rombeallo, Yulianus (UNES Law Review, 2024)
Narcotics rehabilitation is an effort to free narcotics users from the trap of addiction to narcotics abuse. In the concept of restorative justice, someone who commits a crime does not have to be sentenced to prison. Imprisonment should act as an ultimum remedium or last resort to punish perpetrators of criminal acts. The concept of applying restorative justice to narcotics cases can be an alternative to punishment through treatment or rehabilitation. However, the next problem is regarding a person's right to apply for and receive rehabilitation as required by law. And next, legal procedures are also required that must be fulfilled by someone who wants to apply for their right to rehabilitation to the authorized agencies such as the National Narcotics Agency and the Courts so that legally someone can claim their right to receive rehabilitation. The research method that the author uses in this research is empirical research. The results of the research confirm that perpetrators of narcotics abuse at the Tana Toraja Regency BNN can be rehabilitated provided that the perpetrators have the awareness to be rehabilitated; positive for using narcotics based on the results of a forensic laboratory examination test if negative, the determination is through an examination by the Integrated Assessment Team; Not a recidivist, dealer and not involved in illicit narcotics trafficking networks; Arrested or caught red-handed without narcotics evidence or with narcotics evidence under 1 gram. Classified as a narcotics addict or victim of narcotics abuse based on the results of the Integrated Assessment Team examination. The legal process for someone who abuses narcotics to receive rehabilitation at the Tana Toraja District BNN has implemented the concept of restorative justice. The legal process is carried out in an integrated manner involving the BNN medical team and legal team. The results of the team's examination will later be used as material for consideration by the panel of judges in handing down legal sentences against perpetrators of narcotics abuse.